Isolation, identification and antibiogram profiles of enterovirulent Escherichia coli from diarrhoeic goat in some selected areas of Rangpur district of Bangladesh - Kamal, Md Rashed; Fakhruzzaman, Md; Akter, Mir Rowshan; Haque, Md Atiqul (Asian Journal of Medical and Biological Research, 2018)
Enterovirulent Escherichia coli remain as an important etiological agent of goat diarrhoea in Bangladesh. The present study was designed with a view to isolate and identifies E. coli from field cases. For this purpose, a total of 135 faecal samples (85 from diarrhoeic and 50 from apparently healthy goat) were collected during the period from January 2012 to July 2012 from different areas in Rangpur District. It was found that the prevalence of E. coli was higher (18.82 %) in diarrhoeic goats while it was lower (14.00 %) in non diarrhoeic goats. Age wise distribution of E. coli isolates were 26.42% in day old to 1 year, 10.53% in 1-2 years and 11.36% in above 2 years age of goat respectively. All the isolates of E. coli revealed greenish black colony with metallic sheen in Eosine methylene blue agar, bright pink color smooth transparent colony in MacConkey agar and slight pinkish smooth colony in Salmonella-Shigella agar. Gram stain and hanging drop techniques were performed with the cultured bacteria. Biochemical properties of the isolates were studied, and antibiotic sensitivity test was done by agar disk diffusion method. In Gram stain, the organisms revealed Gram negative, small rod shaped, occurs singly or paired. Biochemically, all of the isolates showed fermentation of dextrose, sucrose and maltose with the production of acid and gas, negative result to Voges-Proskauer test, positive result to Methylred test and differential result to Indol test. All the isolates of E. coli were highly sensitive to ciprofloxacin and gentamicin while moderately sensitive to colistin, livofloxacin and azithromycin and less sensitive to ceftraexon and tetracyclin and resistant to amoxycillin, ampicillin, erythromycin, and neomycin. Therefore, ciprofloxacin and gentamicin may be the antibiotics of first choice, and colistin, livofloxacin and azithromycin may be the second choice among the test antibiotics for the treatment of illness caused by these bacteria. Asian J. Med. Biol. Res. March 2018, 4(1): 36-43